The Decline of Traditional Sectors in Israel : The Role of the Exchange Rate and the Minimum Wage - Clifton, Eric (IMF Working Papers; Working Paper, 1998)
This paper examines the role of exchange rate appreciation and the minimum wage in the relative decline of traditional sectors in Israel. It finds little evidence to indicate that real exchange rate appreciation is primarily responsible for this decline. Rather, the evidence indicates that slower productivity growth in traditional sectors has led to relatively larger increases in unit labor costs compared with high-tech sectors. Although the links are only indicative, the evidence also suggests that the minimum wage has played a role in the relatively faster growth in unit labor costs.